A Large Pleural Effusion following Abdominal Aortic Surgery - Vinoo K. Ramsaran; Vandana K. Seeram; James Cury; Adil Shujaat (Case Reports in Pulmonology)
Chylous ascites and coexistent chylothorax is a rare but important complication following retroperitoneal abdominal surgery. We report a 70-year-old male who developed gradual abdominal distension, chest tightness, and dyspnea five months after having an uncomplicated aortobifemoral bypass performed. Physical examination was consistent with a large right sided effusion and ascites which were confirmed by computed tomography. Thoracentesis yielded an opaque milky fluid with analysis consistent with a chylothorax with a paracentesis revealing fluid that was similar in both appearance and biochemistry. The patient failed initial conservative management so a chest tube was placed followed by chemical pleurodesis. We review the literature of the pathophysiology and treatment approach to such a pleural effusion.